Analysis of Community Participation in Development in Lingat Village, Selaru District, Tanimbar Islands Regency. - Redrik Hirohito Lethulur; Josep A. Ufi; La Madjid (PT. Banjarese Pacific Indonesia, 2024)
This research was conducted in Lingat Village, Selaru District, Tanimbar Islands Regency. Primary data collection was carried out through interviews with a number of informants who were considered to be directly involved in the development processes taking place in Lingat Village. The results of this research show that first, the participation of personnel from the Lingat village community in development programs taking place in Lingat village is still minimal because the community's awareness of responsibility for development programs is low for which people are willing to work if they are given wages. Second, there are also material participants from the Lingat village community who give for free or willingly, but there are also those who give by asking for something in return. Third, community participation in maintaining and enjoying development in Lingat village is good, because the community participates in enjoying the results of development in the village, for this reason the Lingat village community is responsible for maintaining development in Lingat village so that it can be used together.Based on the results of the research above, the Lingat village government is advised to look at and follow up on these matters by providing socialization to the Lingat village community about the responsibilities, rights and obligations of the community in every development program that occurs in the village, especially in Lingat village, Selaru sub-district. Tanimbar Islands Regency.